Comparison of Perceptions of Skin Condition, Product Use and Allergen Reactivity Between People with Psoriasis and Controls in the European Dermato-Epidemiology Network (EDEN) Fragrance Study - Fortunato Cassalia; Simone Cazzaniga; Robert Ofenloch; Peter Elsner; Margarida Gonçalo; Marie-Louise Schuttelaar; Åke Svensson; Elena Pezzolo; Magnus Bruze; Luigi Naldi (Acta Dermato-Venereologica, 2024)
Psoriasis, a chronic inflammatory skin disease, goes beyond visible symptoms and affects the general well-being of patients. The aim of this study is to understand how patients with psoriasis perceive their skin characteristics and reactivity to allergens. The study population includes 11,283 participants within the European Dermato-Epidemiology Network (EDEN) Fragrance study, covering several European regions. The study compared perceptions of skin dryness, sensitivity, product avoidance and reactivity to allergens between patients with psoriasis and controls, evaluating the potential influence of psoriasis severity. The results showed that subjects with psoriasis reported dry skin (71.1%) and sensitive skin (49.4%) more often than did controls (51.6% and 38.5%, respectively). Psoriasis patients were more likely to avoid specific products. Interestingly, there were no significant differences in patch-test results between the 2 groups and the severity of psoriasis did not have a consistent impact on these perceptions. In conclusion, people with psoriasis tend to perceive their skin as drier and more sensitive. Notably, the severity of psoriasis did not consistently influence these perceptions and objective reactivity to allergens did not align with subjective perception. Understanding these aspects is crucial for tailoring treatments to improve the well-being of patients with psoriasis, which warrants further research to explore subjective perceptions of skin well-being in patients with psoriasis.